Prevalence and Factors Associated with Subclinical Left Ventricular Systolic Dysfunction Evaluated by Mid‐Wall Mechanics in Rheumatoid Arthritis. Issue 9 (18th February 2016) - Cioffi, Giovanni; Viapiana, Ombretta; Ognibeni, Federica; Fracassi, Elena; Giollo, Alessandro; Adami, Silvano; Gatti, Davide; Mazzone, Carmine; Faganello, Giorgio; Lenarda, Andrea Di; Rossini, Maurizio
Abstract : Objective: Patients with rheumatoid arthritis (RA) have an increased cardiovascular event rate, mainly due to the arterial stiffness which leads to coronary atherosclerosis and concentric left ventricular (LV) geometry. These conditions predispose to LV systolic dysfunction (LVSD), which can be detected by stress‐corrected mid‐wall shortening (sc‐MS), an early prognosticator of cardiovascular events in asymptomatic patients with arterial hypertension and/or diabetes. In these subjects, sc‐MS is frequently impaired even though LV ejection fraction (LVEF) is preserved. In this study, we analyzed the prevalence and the factors associated with asymptomatic LVSD measured by sc‐MS among patients with RA and verified whether RA per se was independently related to LVSD. Methods: We prospectively recruited 198 outpatients with RA without overt cardiac disease between January and June 2014 and compared them to 198 controls matched for age, gender, body mass index, and prevalence of hypertension and diabetes. sc‐MS was taken as index of LVSD and considered impaired if <86.5%. Results: Impaired sc‐MS was detected in 110 (56%) RA patients and in 30 (15%) controls (P < 0.001), whereas LVEF was impaired (value <50%) in six (3%) RA patients and in two (1%) controls (P = ns). Multiple logistic regression analysis revealed that RA was independently associated with impaired sc‐MS (Exp β 2.01 [CI 1.12–3.80], P = 0.02) together with increased LV mass and concentric geometry. Conclusions: More than half RA patients without overt cardiac disease have LVSD detectable by sc‐MS. RA emerges as a condition closely related to LVSD. These findings might explain the high risk for adverse cardiovascular events in RA patients.